2007
DOI: 10.1109/lcomm.2007.061589
|View full text |Cite
|
Sign up to set email alerts
|

Outage optimality of opportunistic amplify-and-forward relaying

Abstract: Abstract-In this paper, we show that optimal selection and transmission of a single relay among a set of multiple amplifyand-forward (AF) candidates minimize the outage probability (i.e., outage-optimal) and outperform any other strategy that involves simultaneous transmissions from more than one AF relay under an aggregate power constraint. This outage optimality demonstrates that cooperation benefits are maximized with intelligent scheduling among AF relays.Index Terms-Cooperative diversity, fading relay cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
2
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(62 citation statements)
references
References 6 publications
2
51
2
7
Order By: Relevance
“…This is a typical assumption used in many references, such as in [13,18,23,24], considering cooperative relays. In this case, the total power P = 1 is only consumed by the first (S-R) and second (R-D) hops.…”
Section: Icrpmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a typical assumption used in many references, such as in [13,18,23,24], considering cooperative relays. In this case, the total power P = 1 is only consumed by the first (S-R) and second (R-D) hops.…”
Section: Icrpmentioning
confidence: 99%
“…In addition to BER/SER, the outage probability of cooperative wireless systems has been investigated, for example, in [16][17][18][19]. In more detail, the lower and asymptotic bounds of outage probability have been derived in [16] for dual-hop relay networks experiencing Rayleigh fading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [5] showed that this scheme has the same diversity order as the cooperative diversity using space-time-coding [6] in terms of the outage probability for both decode-and-forward and amplify-and-forward schemes. However, this important result was given using semi-analytical asymptotic analysis at high SNR only (without deriving a closed-form expression for the outage probability).Many different schemes for single relay selection have been proposed in [5], [7]- [9]. The authors in [10] analyzed the adaptive DAF relaying technique where among N relays that can participate, only k relays (k <N ), with good channels to the source decode and forward (retransmit) the source information to the destination.…”
Section: Introductionmentioning
confidence: 99%
“…Semakin rendah outage probability yang didapatkan, maka throughput dan efisiensi spektral juga akan semakin meningkat [11]. Penggunaan mode full-duplex untuk memperoleh efisiensi spektral yang tinggi telah dikaji pada penelitian sebelumnya [12].…”
unclassified